PENYELARASAN STRATEGIS VISI-MISI DALAM PENGUATAN TATA KELOLA MADRASAH: STUDI KASUS MI AL-MUHAJIRIN PURWAKARTA - Nadiya, Asma; Hima Fatimah Nurusyifa (Epistemic: Jurnal Ilmiah Pendidikan, 2026)
Vision and mission statements in madrasahs are often reduced to symbolic artefacts, with limited translation into operational practices. Despite theoretical emphasis on strategic alignment and collaborative governance, empirical evidence on how such alignment is operationalized in value-based Islamic education remains limited. This study examines how participatory mechanisms mediate the transformation of vision–mission statements into institutional practices. Using a qualitative single-case design at MI Al-Muhajirin Purwakarta (n = 5), data were collected through interviews, observation, and document analysis, and analyzed iteratively. Findings reveal a dynamic alignment process involving participatory deliberation, institutionalization through RKAM linking vision to indicators and resources, pedagogical translation in classrooms, and recursive monitoring supported by instructional leadership. Islamic values function not only as cultural norms but as governance mechanisms shaping decision-making. However, alignment is constrained by uneven teacher capacity and weak monitoring systems. This study advances normative-strategic alignment and offers practical insights for strengthening value-based governance in madrasah management.